Examining The Impact Of Team Communication Practices In Innovative Research And Development R&D Teams : An Early Findings - Md Saad, Mohd Shamsuri; Abdul Majid, Izaidin; Jano, Zanariah; Md Nordin, Shahrina (MCSER Publishing, 2014)
-